Emission of a Compression Ignition Engine Fuelled by Diesel and Imitated Syngas - Mahgoub, B. K. M. (2011)
Biomass can be converted into a useful source of energy through gasification. The gasification product, known as synthesis gas or syngas, composition of syngas may fluctuate due to many factors such as operational errors of the gasifier as well as the type of feedstock used or may be due to the feeding rate fluctuation. Therefore it would be difficult to assess the effect of syngas composition and diesel replacement ratio to the emission when combusted in dual fuel syngas – diesel compression ignition engine. In order to overcome this problem controllable composition and conditions of imitated syngas was used in this study by selective three compositions of syngas close to the real conditions. The objective of this study is to determine the exhaust emissions of a compression ignition engine fuelled with diesel and imitated syngas at different compositions and diesel replacement ratios to determine the most appropriate composition of syngas and diesel replacement ratio which will give less emission. The test results on syngas emission are compared with the results of diesel. CO2 and NOX emission level was reduced on syngas dual fuel mode, but there were increases in CO and THC emissions throughout all syngas compositions examined due to poor combustion efficiency of dual fuel operation.